From H1N1 to COVID-19: What we have seen in children with hemoglobinopathies (Clinics, 2022)
This work aimed to better understand the impact of pandemics of respiratory viruses on children with hemoglobinopathies through a comprehensive review of the literature. MEDLINE, SCIELO, LILACS, and PUBMED were used as data sources to find articles without time period restrictions. Previous observations suggest that patients with hemoglobinopathies are a group especially susceptible to the complications of viral respiratory infections, with greater morbidity and mortality related to them. Within this context, this review found that, during the 2009 H1N1 pandemic, the risk of hospitalization in children and adults increased, especially in patients with a history of complications such as acute chest syndrome. In addition, the Coronavirus Disease 2019 (COVID-19) pandemic appears to have less repercussion among children with hemoglobinopathies compared to adults, similar to what is seen in the general population. In the H1N1 pandemic, patients with hemoglobinopathies behaved as a group more susceptible to complications, with increased morbidity and mortality. However, for COVID-19, the existing data to date on these patients do not show the same clinical impact. Thus, although these children deserve attention in case of infection due to their potential risks, they seem to have a favorable evolution.